1997
DOI: 10.1007/s004300050051
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of human parainfluenza virus-induced cell fusion by pradimicin, a low molecular weight mannose-binding antibiotic

Abstract: Oligosaccharides, especially mannose residues, expressed on the cell surface, are thought to be important for virus-induced membrane fusion. We examined the effect of mannose-binding compounds, pradimicin derivative BMY-28,864 (PRM) and concanavalin A (Con A), on cell fusion of human parainfluenza type 2 virus (hPIV2)-infected HeLa cells. Syncytium formation of hPIV2-infected HeLa cells was suppressed in the presence of Con A. On the other hand, PRM enhanced cell fusion of hPIV2-infected HeLa cells. These effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This surprising result might be explained by a tethering effect of CBA, which might facilitate virus -cell attachment and subsequently productive infection. 47 Indeed, the CBA evaluated in this study are able to bind multiple carbohydrate moieties. 11,12 The role of host cells in determining the sensitivity to CBA was underscored by the observed altered sensitivity of genetically identical viruses, which were propagated on different cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…This surprising result might be explained by a tethering effect of CBA, which might facilitate virus -cell attachment and subsequently productive infection. 47 Indeed, the CBA evaluated in this study are able to bind multiple carbohydrate moieties. 11,12 The role of host cells in determining the sensitivity to CBA was underscored by the observed altered sensitivity of genetically identical viruses, which were propagated on different cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the highly specific interaction of lectins with sugars would point out for the possibility of positive or negative modulation of virus binding to host cells. As previously described, lectins have been used as valuable tool for monitoring virus (Becht et al, 1972;Okada & Kim, 1972;Ito & Barron, 1974;Poste et al, 1974;Cartwright, 1977;Takehara, 1979;Khélifa & Menezes, 1982;Conti & Tsiang, 1985;Okamoto et al, 1997). On the other hand, a few data are available concerning the effect of ConA on the replication of nonenveloped viruses (Okada & Kim, 1972;Ito & Barron, 1974;Lonberg-Holm, 1975 Kopecky et al, 1991;Okamoto et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Concanavalin A (ConA), a lectin from jack bean, binds specifically to mannosyl and glycosyl residues. This lectin has been extensively used for the study of virus attachment to host cells and characterization of glycoproteins involved, mainly concerned to the enveloped viruses (Calafat & Hageman, 1972;Okada & Kim, 1972;Miki, 1980;Conti & Tsiang, 1985;Grail & Norval, 1986;Kopecky et al, 1991;Okamoto et al, 1997). Svensson (1984) demonstrated that RV express mannosyl residues in VP7.…”
Section: Introductionmentioning
confidence: 99%